2013
DOI: 10.1111/jocn.12309
|View full text |Cite
|
Sign up to set email alerts
|

Personal awareness and behavioural choices on having a stoma: a qualitative metasynthesis

Abstract: The description and interpretation on personal awareness and behavioural choices associated with having a stoma is useful for nurses in providing practical, informational and emotional supports to help the individuals successfully adapt to their lives with a stoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 35 publications
1
9
0
6
Order By: Relevance
“…Others may consider that it is difficult to take good care of themselves, which emphasised individuals' efforts to manage ostomy, including the assessment of a stoma, the prevention of complications and the use of stoma appliances independently (Bohnenkamp et al, 2004). Additionally, many Chinese are keen on face-saving and are ashamed of living with an ostomy, so they are unwilling to take the responsibility for self-care (Tao, Songwathana, Isaramalai, & Zhang, 2014). As the individuals adapt to their new life with a stoma gradually, they made efforts to improve their self-management abilities and reduce the negative impacts of the ostomy on themselves and their families (Thorpe, Mcarthur, & Richardson, 2014).…”
Section: Effects Of Intervention On the Stages Of Change Of Self-mamentioning
confidence: 99%
“…Others may consider that it is difficult to take good care of themselves, which emphasised individuals' efforts to manage ostomy, including the assessment of a stoma, the prevention of complications and the use of stoma appliances independently (Bohnenkamp et al, 2004). Additionally, many Chinese are keen on face-saving and are ashamed of living with an ostomy, so they are unwilling to take the responsibility for self-care (Tao, Songwathana, Isaramalai, & Zhang, 2014). As the individuals adapt to their new life with a stoma gradually, they made efforts to improve their self-management abilities and reduce the negative impacts of the ostomy on themselves and their families (Thorpe, Mcarthur, & Richardson, 2014).…”
Section: Effects Of Intervention On the Stages Of Change Of Self-mamentioning
confidence: 99%
“…Previous studies of health-related quality of life [4,5,6,7] in people receiving stoma-forming surgery and one meta-synthesis [52] have found that stoma-forming surgery has a dramatic impact on post-operative adjustment in terms of poor self-image and individuals feeling out of control of their bodies and their lives. However, a deeper understanding of meaning to those experiencing stoma formation has been largely absent.…”
Section: Introductionmentioning
confidence: 99%
“…Den har ikke lengre de samme funksjoner, og den oppleves ikke som hel. (4,6,7,10). Kroppen kan oppleves som fremmed, og noen har en negativ kroppsfølelse og distanserer seg fra kroppen sin.…”
Section: Studier Om Voksneunclassified
“…Kroppen kan oppleves som fremmed, og noen har en negativ kroppsfølelse og distanserer seg fra kroppen sin. Det er beskrevet at den «nye kroppen» gjør at personen føler seg annerledes enn andre (6). Det å få en stomi innebaerer en stor endring som påvirker personens livssituasjon, selvbilde, kroppsbilde og kroppsfølelse (4, 6-8, 10-12).…”
Section: Studier Om Voksneunclassified
See 1 more Smart Citation